The Perpendiculum: Presumptions and Legal Arguments in the 12th Century - Concilio, David De (Late Antiquity and Medieval Studies E-Books Online, Collection 2024., 2025)
The Perpendiculum (or Summula de presumptionibus ), produced in Northern France c.1170, is one of the earliest collections of brocards: a literary genre intended to provide legal arguments for disputation in the medieval schools of law. Its innovative use of dialectical techniques and its theorization of canon law presumptions have attracted the attention of legal historians, raising questions on its origin and milieu. This book offers the first comprehensive study of this work, with a Latin edition and an English translation of its text, shedding new light on the significance of this collection for twelfth-century legal teaching and learning.